(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This article projects women who shares more comprehensive account on Egyptian culture and heritage. In ancient Egypt, women were very powerful and highly respected in their community than men. In the early human history, women also hunted and foraged; as human settlements formed, then participated in activities outside the home, and ran flourishing politics. Michelle Moran dives deep into the history of various nations through her novels to represent women as powerful. In The Heretic Queen, Moran explores the women`s power structure and authority of ancient Egypt. Moran depicts the characters to portray the complex hierarchies of power, showcasing how power influences everything from individual relationships to broader socio- political structures. Moran transforms stone-cold history into a magical narrative of Egypt`s past. Her characters live in an empire where wealth and power are immense, and survival depends on aligning oneself with the right people in authority. In the historical novel Michelle Moran`s The Heretic Queen, the firm structure of Egyptian royalty is highlighted by wealth and power, a cultural aspect where authority and hierarchy are deeply ingrained and unchallenged.